The Correspondence of Wolfgang Capito - Capito, Wolfgang (University of Toronto Press, 2016)
Wolfgang Capito (1478-1541), a leading Christian Hebraist and Catholic churchman who converted to Protestantism, was a pivotal figure in the history of the Reformation. After serving as a professor of theology in Basel and adviser to the archbishop of Mainz, he moved to Strasbourg, which became, largely due to his efforts, one of the most important centres of the Reformation movement after Wittenberg. This penultimate volume in the series is a fully annotated translation of Capito's existing correspondence covering the years 1532-36 and culminating in the Wittenberg Concord between the Lutheran and Reformed churches. The correspondence includes Capito's efforts, alongside those of his colleague Martin Bucer, to negotiate that compromise. Other letters deal with local, political, financial, and doctrinal questions, as well as Capito's personal life.